1991
DOI: 10.1159/000226950
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sodium Perchlorate and Ionizing Irradiation on the Thyroid Parenchymal and Pituitary Thyrotropic Cells

Abstract: In a 46-week-experiment on 72 female mice the influence of peroral 1.2% sodium perchlorate application, total ionizing irradiation with 8 Gy on 5 consecutive days and their interaction on the pituitary-thyroid axis was studied by histological and stereological methods. It was observed that perchlorate alone caused long-term and strong hypothyroidism with hypertrophic and hyperplastic thyroid epithelial cells as well as pituitary thyrotropic cells. When only irradiation was used, no uniform changes in the struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Ammonium perchlorate has been tested in a battery of in vitro and in vivo genotoxicity tests; perchlorate does not appear to be mutagenic or clastogenic ( OEHHA 2004 ). A number of animal studies have shown that perchlorate at high doses (> 1,300 mg/kg/day) causes thyroid tumors in rodents ( Gauss 1972 ; Kessler and Kruskemper 1966 ; Pajer and Kalisnik 1991 ). Because the occurrence of the tumors was preceded mostly by signs of thyroid hormone disruption and thyroid enlargement, these tumors are generally interpreted as being secondary to the anti-thyroid effects of perchlorate [ OEHHA 2004 ; U.S. Environmental Protection Agency (U.S. EPA) 2002 ].…”
Section: Animal Toxicity Datamentioning
confidence: 99%
“…Ammonium perchlorate has been tested in a battery of in vitro and in vivo genotoxicity tests; perchlorate does not appear to be mutagenic or clastogenic ( OEHHA 2004 ). A number of animal studies have shown that perchlorate at high doses (> 1,300 mg/kg/day) causes thyroid tumors in rodents ( Gauss 1972 ; Kessler and Kruskemper 1966 ; Pajer and Kalisnik 1991 ). Because the occurrence of the tumors was preceded mostly by signs of thyroid hormone disruption and thyroid enlargement, these tumors are generally interpreted as being secondary to the anti-thyroid effects of perchlorate [ OEHHA 2004 ; U.S. Environmental Protection Agency (U.S. EPA) 2002 ].…”
Section: Animal Toxicity Datamentioning
confidence: 99%
“…The primary target tissue for perchlorate toxicity is the thyroid gland as indicated by perturbations of T 3 , T 4 , and TSH hormones and by thyroid histopathology. Benign tumors and follicular cell carcinomas have been reported in the thyroid of male Wistar rats and female BALB/c mice treated with repeated, high dose exposures (2 years at 1,339 and 46 weeks at 2,147 mg/kg/day, respectively) of potassium perchlorate in drinking water (24,37). The majority of human data are clinical reports of patients treated with potassium perchlorate for hyperthyroidism resulting from Graves disease, an autoimmune condition.…”
Section: Histopathologymentioning
confidence: 99%
“…not evaluate the effects of long-term exposures to perchlorate on reproduction or behavior. In animals, long-term studies clearly show thyroid toxicity at high doses (1% potassium or sodium perchlorate in drinking water), but these studies generally did not examine targets other than the thyroid (Kessler and Krunkemper 1966;Pajer and Kalisnik 1991). No adequate developmental toxicity study in rats has been conducted to date.…”
mentioning
confidence: 99%